Non-invasive Diagnostic Tests in Cystic Fibrosis-Related Liver Disease: A Diagnostic Test Accuracy Network Meta-Analysis - Martonosi, Ágnes Rita; Soós, Alexandra; Rumbus, Zoltán; Hegyi, Péter; Izsák, Vera; Pázmány, Piroska; Imrei, Marcell; Váncsa, Szilárd; Szakács, Zsolt; Párniczky, Andrea (Frontiers in Medicine, 2021)
Background and aims: Cystic fibrosis-related liver disease (CFLD) is one of the leading causes of morbidity and mortality in cystic fibrosis (CF). Several non-invasive diagnostic methods have been proposed as screening tools for CFLD. Our aim was to rank all available non-invasive diagnostic modalities diagnostic performance. Methods: A systematic search was performed in five medical databases to find studies which reported on any single or composite non-invasive diagnostic test (as index test) compared to the Debray, the EuroCare or the Colombo criteria (as reference standard). Ranking was carried out with a Bayesian diagnostic test accuracy network meta-analysis based on superiority indices, calculated from pooled sensitivity (Se) and specificity (Sp) with 95% confidence interval (CI). The study was registered under CRD42020155846 in PROSPERO. Results: 15 studies with 15 index tests and the combination of them were included. The New criteria had the best performance for detecting CFLD (Se:94%[CI:58-100],Sp:72%[CI:52-84]) while transient elastography (Se:65%[CI:56-74],Sp:88%[CI:84-91]) and its combination with tissue inhibitor of metalloproteinase-4 measurement (Se:78%[CI:30-100],Sp:64%[CI:18-95%]) proved to be the second and third best options. In the subgroup of imaging techniques, transient elastography (Se:66%[CI:57-72],Sp:88%[CI:85-91%]), acoustic radiation force impulse in the right lobe (Se:54%[CI:33-74],Sp:88%[CI:66-96]) and that in the left lobe (Se:55%[CI:23-81],Sp:82%[CI:50-95]) were ranked the highest. Comparing biochemical markers/fibrosis indices, the measurement of Forns index (Se:72%[CI:25-99],Sp:63%[CI:16-94]), aspartate aminotransferase-to-platelet ratio (Se:55%[CI:41-68],Sp:83%[CI:66-89]) and alkaline phosphatase (Se:63%[CI:18-93],Sp:64%[CI:19-95]) were ranked the highest. Conclusion: The New criteria has the best diagnostic performance. In clinical practice, transient elastography seems to be a simple, cheap and non-invasive tool outperforming imaging, biochemical and fibrosis tests for detecting CFLD. Further studies are needed to validate our findings.